Adaptive management of natural resources: theory, concepts, and manage ment institutions. - Stankey, George H.; Clark, Roger N.; Bormann, Bernard T. (U.S. Department of Agriculture, Forest Service, Pacific Northwest Rese arch Station, 2005)
This report reviews the extensive and growing literature on the concep t and application of adaptive management. Adaptive management is a cen tral element of the Northwest Forest Plan and there is a need for an i nformed understanding of the key theories, concepts, and frameworks up on which it is founded. Literature from a diverse range of fields incl uding social learning, risk and uncertainty, and institutional analysi s was reviewed, particularly as it related to application in an adapti ve management context. The review identifies opportunities as well as barriers that adaptive management faces. It concludes by describing st eps that must be taken to implement adaptive management.